Corel paint shop pro X : digital darkroom - Clark, Michael T. (Sams, 2006)
Corel Paint Shop Pro X Digital Darkroom is an easy-to-follow, tutorial approach to using Paint Shop Pro in exactly the way home users want to use it - to manipulate your own images in ways that a local photo lab often does to create both practical and comical projects. As you read, you will actually use the program to complete a variety of projects. You'll learn about key Paint Shop Pro tools almost without trying through both traditional and contemporary projects. Indulge in shrinking the kids, performing digital plastic surgery, modifying vehicles, creating creatures the tabloids would love to profile, altering pets, creating trading cards and calendars, and combining images to create once-in-a-lifetime shots. Drop people into places they've never been and challenge Mother Nature with unique perspectives. Create holiday magic, photo montages, and even do some traditional photo manipulation. Author T. Michael Clark provides careful instruction that will allow you, whether you are a novice or experienced Paint Shop Pro user, to complete projects and enjoy your experience with Paint Shop Pro X.